Dental Student Evaluation in the Predoctoral Comprehensive Care Clinic: II. Quarterly (Formative/Summative) and Final (Summative) Evaluation - Cheryl Straub-Morarend; Michael Spector; David Johnsen; David Holmes (Association of American Medical Colleges, 2013)
Abstract This resource was created to support faculty assessment of dental student performance in the predoctoral comprehensive care clinic. This resource consists of an instructor's guide, the quarterly student evaluation by faculty form, the quarterly student self-evaluation form, and the criteria for the final course grade. At approximately 10 week intervals, each faculty member that has worked with the student in clinical patient contact completes the quarterly evaluation form, noting a subjective assessment of each student's current status with regard to each of the six domains and adding written comments regarding the student's strengths and weaknesses, as well as suggestions for professional growth. At the same point in time, the student will complete the quarterly student self-evaluation form and submit it to the group leader. The group leader compiles all the evaluations of the faculty; student progress is discussed together amongst faculty in faculty conferences each 10 weeks throughout the course. After each faculty conference, the group leader provides students with formal face-to-face individual feedback regarding current grade status, perceived strengths, shortcomings, and suggestions for professional growth. At these meetings, the group leader and the student also review the student's self-evaluation form, with particular focus on how this self-evaluation compares with the faculty assessments. The forms and protocols included here were developed and refined specifically for use in the Family Dentistry program at the University of Iowa College of Dentistry. These assessment tools were created to guide learning, reinforce learning, and to support dental student evaluation in the predoctoral comprehensive care clinic. The forms and protocols presented here have been in use in our clinical program since 2007. They are reviewed and refined annually, and have proven to be effective in achieving our objectives.